Pertumbuhan dan Kadar Alkaloid Tanaman Leunca (Solanum americanum Miller) pada Beberapa Dosis Nitrogen - Marchella Putriantari; Edi Santosa (Jurnal Hortikultura Indonesia, 2014)
ABSTRACTLeunca fruit is indigenous vegetable and widely used as vegetables mainly in West Java. In order to improve productivity and quality, several levels of nitrogen was used.  The objective of the experiment  was  to determine  the effect  of  nitrogen  level  on  growth  and  productivity, and on  the alkaloid levels. The experiment was conducted at Leuwikopo Experimental Station IPB in December 2013  -  April 2014. Experiment was arranged in a  Randomized Complete Block Design with single factor and four replications. Nitrogen fertilizer consisted  of four levels, i.e., 0  kg N ha-1, 60 kg  N ha-1,  120  kg  N ha-1,  and  180  kg  N  ha-1. The  results  showed  that  growth  and productivity were affected  by nitrogen  application. The highest  productivity of Leunca  was  obtained  by  nitrogen fertilizer at rate of 180  N ha-1, and the highest alkaloid content was produced by plant treated with 60 kg N ha-1. The highest productivity of fruits was 18 445 kg ha-1.Key words: alkaloid, indigenous vegetable, productivity, Solanum nigrum, nitrogen dosage ABSTRAKBuah  leunca  merupakan  sayuran  indigenous  terutama  bagi  masyarakat Jawa  Barat.  Dalam rangka  meningkatkan  produktivitas  dan  kualitas  buah leunca,  perlu  dilakukan  kajian  budidaya khususnya  pemupukan.  Penelitian ini bertujuan  menentukan  dosis  pupuk  nitrogen  terbaik  untuk meningkatkan pertumbuhan  dan  produktivitas  tanaman  leunca,  serta  mengkaji  pengaruh pupuk nitrogen terhadap kadar alkaloid tanaman leunca. Percobaan ini dilaksanakan di Kebun Percobaan Leuwikopo IPB pada bulan Desember 2013  - April 2014. Percobaan ini menggunakan Rancangan Kelompok Lengkap Teracak satu faktor dengan empat ulangan. Faktor dosis pupuk nitrogen terdiri atas empat  taraf,  yaitu  tanpa  pupuk  N,  60  kg  N  ha-1,  120  kg  N  ha-1,  dan 180  kg  N  ha-1.  Hasil penelitian  menunjukkan  bahwa  pertumbuhan  dan produktivitas  tanaman  terbaik  dihasilkan  oleh perlakuan  dosis  pupuk nitrogen  180  kg  N  ha-1.  Kadar  alkaloid  tertinggi  dihasilkan  tanaman dari perlakuan dosis pupuk nitrogen 60 kg N ha-1. Produktivitas buah leunca mencapai 18 445 kg ha-1.Kata kunci: alkaloid, produkvitas, sayuran indigenous, Solanum nigrum, dosis nitrogen